A MYCOLOGICAL STUDY OF CLINICAL SAMPLES FROM SUSPECTED MYCOSES IN A TERTIARY CARE HOSPITAL - Devrari, Jitendra Chandra; Saxena, Varsha; Pai, Vidya (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of this study was to isolate and identify the fungal agents obtained from clinical samples of suspected mycoses patients attending Yenepoya hospital. Methods: Various clinical samples obtained from patients were subjected to preliminary examination according to standard mycological protocols such as KOH mount, wet mount, Gram’s staining, and Indian ink examination. Causative organisms were identified by macroscopically and microscopically after growth on sabouraud’s dextrose agar (with or without cycloheximide and chloramphenicol) and confirmed by lactophenol cotton blue mount, slide culture technique, urease test, and growth on chrome agar accordingly. Results: Of 274 clinical samples, 125 were culture positive in which the fungal isolates obtained were dermatophytes (all 3 genera), Candida species (including Candida albicans), Fusarium species, Aspergillus fumigatus, and Cryptococcus neoformans. Male predominance was found among the patients being 6:3 male:female ratio. Conclusion: Among the superficial infection, Trichophyton mentagrophytes was found to be predominant isolates; however, in systemic infection, C. albicans was the predominant isolates.